Remittance in Niger: Effects on economic growth and on migrants' left behind - Issoufou Oumarou (Croatian Review of Economic, Business and Social Statistics (CREBSS), 2021)
Remittances have long been an important source of revenue for many people in the Republic of Niger. In order to fight poverty, young people choose to migrate. In 2019, a total of 293 million U.S. dollars was sent by migrants to their relatives in Niger; that is 3% of Niger Gross Domestic Product (GDP). The objective of this study is to analyze the effects of remittances on economic growth in Niger and the significance of its contribution in improving the living condition of migrants' left behind families. The study applies a three-step econometric procedure followed by a survey on the usage of the remittances in the city of Tahoua (Republic of Niger). The study also performed some tests on the residuals for the accuracy of the prediction of the model. The empirical results showed no long run relationship between remittances, economic growth and gross fixed capital formation in Niger. However, in the short-run, the study revealed the existence of causal effect between remittances and economic growth. On the other hand, the results of the conducted survey in the city of Tahoua showed that 45.7% of the received remittance is used in food expenditure, 19.3% in education expenditure, 10.36% in health expenditure and 5.4% is allocated to house rent. The survey also revealed the importance of the remittances for the left behind. It indicates that 14% of the respondent left behind wish to see another family member engage in migration.
Keywords: C32; F24; F43; O15; 330; economic growth; left behind; Niger; remittance; Tahoua